Sub-Optimal Dry Land Management: Potential for Local Food Cultivation of Dioscorea sp. (Gembili) to mitigate food security in Sukoharjo Regency, Central Java - Fitria, Anita Dwy; Helbawanti, Octaviana; Yuliyani, Leny; Nuryaman, Hendar; Hakim, Abdul; Benatar, Gilang Vaza (Plantropica: Journal of Agricultural Science, 2024)
Land in Tawangsari District, Sukoharjo Regency had a limiting factor in the form of water availability. One of the local commodities cultivated for generations on dry land in this region is gembili (Dioscorea sp.). However, the gembili cultivation process has not produced optimal productivity and is threatened with extinction. Therefore, gembili cultivation and use of dry land need to be optimized by carrying out integrated land management. The aim of utilizing dry land is to increase local food production and sustainability as alternative food and maintain national food security. This research was conducted using data on productivity, quantity and type of fertilizer obtained through interviews with gembili farmers and secondary data on soil types obtained from BPP Tawangsari District, Sukoharjo Regency. The results showed that grumusol and lithosol soil types had no significant effect (p > 0.05) on gembili productivity. Providing organic + inorganic fertilizer with giving organic fertilizer without a combination produced values that were not significantly different (p > 0.05). However, the average productivity results were sequentially from grumusol and lithosol (6.1 ton.ha-1 and 7.1 ton.ha-1). Meanwhile, the use of organic fertilizer is 8.06% higher compared to organic fertilizer + inorganic fertilizer. The results of the multiple regression test for organic fertilizer had a significant effect (p < 0.05) on the productivity of Dioscorea sp..